Institutional Co-Evolution and Hybrid Regulation in the Digital Economy: A Case Study of BRICS Nations - Shkalenko, Anna V.; Kozlova, Svetlana A.; Nazarenko, Anton V. (Ital Publication, 2025)
This study investigates the institutional co-evolution associated with digitalization processes in BRICS countries, emphasizing the development of hybrid regulatory frameworks that integrate state intervention, platform-based self-regulation, and entrepreneurial institutional agency. The primary objective is to analyze how these frameworks operate within heterogeneous governance environments and address the sustainability challenges arising in emerging digital economies. Grounded in the theory of institutional co-evolution, the research applies a mixed-methods design, combining bibliometric mapping, comparative policy analysis, and multiple linear regression on cross-national panel data from Brazil, Russia, India, China, and South Africa (2018 - 2022). The findings demonstrate that increasing levels of digitalization and innovation are significantly correlated with reductions in environmental risks, while GDP growth remains positively associated with CO2 emissions; underscoring a structural tension between economic expansion and ecological resilience. To address this contradiction, the study proposes and empirically validates an Optimized Hybrid Model of institutional regulation, which improves sustainability indicators by 18.5%. The novelty of this research lies in the operationalization of institutional co-evolution within digital governance, offering a transferable policy model for flexible, adaptive regulation in complex, data-intensive economies. These results contribute to the advancement of institutional theory and provide actionable insights for the governance of transitional digital systems.